The Operational Efficiency of Administrative Officers in Governance and Public Order Maintenance: A Case Study of Phon Thong District, Roi Et Province: The Operational Efficiency of Administrative Officers in Governance and Public Order Maintenance: A Case Study of Phon Thong District, Roi Et Province - Meesiri, Thanapol; Promphoonga, Jirapon (RATANABUTH JOURNAL, 2026)
This study aimed to: (1) examine the level of operational efficiency in governance and public order maintenance of local administration officers; and (2) compare operational efficiency according to personal factors, namely gender, age, marital status, educational attainment, monthly income, and length of service. This study employed a quantitative research design. The population consisted of 696 individuals, including village headmen, village headmen deputies in administrative affairs, village headmen deputies in security maintenance, assistant subdistrict headmen, and subdistrict medical officers in Phon Thong District, Roi Et Province. The sample size was determined using Yamane’s formula, yielding 254 respondents. The research instrument was a questionnaire with a reliability coefficient of 0.90. Data were analyzed using descriptive statistics, namely frequency, percentage, mean, and standard deviation, as well as inferential statistics, namely the independent samples t-test and one-way analysis of variance (One-way ANOVA), with statistical significance set at the .05 level. The research findings revealed that: 1) the overall operational efficiency in administration and maintenance of peace and order of administrative officers in Phon Thong District, Roi Et Province, was at a high level (= 4.08, S.D.=0.83) 2) the comparative analysis of operational efficiency indicated that administrative officers of different genders exhibited a statistically significant difference in operational efficiency at the .05 level, with male officers demonstrating a higher mean score than female officers. Conversely, differences in age, marital status, educational attainment, monthly income, and length of tenure did not result in a significant difference in operational efficiency. This indicates that gender was the sole personal factor influencing the variance in operational efficiency regarding administration and maintenance of peace and order among administrative officers in the study area.